2018
DOI: 10.1136/bmj.j5492
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension: pathogenesis and clinical management

Abstract: Pulmonary hypertension is defined as a resting mean pulmonary artery pressure of 25 mm Hg or above. This review deals with pulmonary arterial hypertension (PAH), a type of pulmonary hypertension that primarily affects the pulmonary vasculature. In PAH, the pulmonary vasculature is dynamically obstructed by vasoconstriction, structurally obstructed by adverse vascular remodeling, and pathologically non-compliant as a result of vascular fibrosis and stiffening. Many cell types are abnormal in PAH, including vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
638
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(658 citation statements)
references
References 241 publications
7
638
0
13
Order By: Relevance
“…While abnormalities of mitochondrial metabolism, notably a shift to aerobic glycolysis called the Warburg phenomenon, contribute to the proliferation/apoptosis imbalance in cancer, this study focuses on developing therapeutic agents that target another, more recently recognized abnormality, namely dysregulation of mitochondrial dynamics. 7 This suggests the RV dysfunction, which is commonly the cause of mortality in PAH, 22 may in part be due to mitochondrial fission. 10,11 Inhibition of Drp1 triggers a cell cycle checkpoint and results in cell cycle arrest and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While abnormalities of mitochondrial metabolism, notably a shift to aerobic glycolysis called the Warburg phenomenon, contribute to the proliferation/apoptosis imbalance in cancer, this study focuses on developing therapeutic agents that target another, more recently recognized abnormality, namely dysregulation of mitochondrial dynamics. 7 This suggests the RV dysfunction, which is commonly the cause of mortality in PAH, 22 may in part be due to mitochondrial fission. 10,11 Inhibition of Drp1 triggers a cell cycle checkpoint and results in cell cycle arrest and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…21 We have shown previously that there is a basal fragmentation of mitochondria in RV myocytes of monocrotaline rats with pulmonary arterial hypertension (PAH), even in the absence of induced IR. 7 This suggests the RV dysfunction, which is commonly the cause of mortality in PAH, 22 may in part be due to mitochondrial fission. Our current results confirm prior studies and demonstrates that inhibiting mitochondrial fission in RV cardiomyocytes by targeting Drp1 decreases mitochondrial ROS production and is cardioprotective ex vivo, evident as a preservation of RV diastolic function 7,8,23 (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) represents an increase in the pulmonary arterial pressure above 25 mmHg, triggered by a progressive rise in pulmonary vascular resistance due to vasoconstriction, vascular remodeling, fibrosis, and inflammation. 1 Several studies have identified the presence of proinflammatory cytokines as promoters of PAH, including interleukins, tumor necrosis factor, and autoantibodies, which advocate for the autoimmune inflammatory pathogenesis of the disease. 2,3 Vessel remodeling and increased vascular resistance in the pulmonary arterial circulation leads to overload of the right cardiac chambers, with right ventricular hypertrophy, tricuspid regurgitation, and subsequent right atrial remodeling, and in case of associated right ventricle ischemia or fibrosis, the evolution is towards right cardiac failure.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…PDE5i might offer a compelling way forward for this purpose. Importantly, PDE5i are a safe and well tolerated class of drug administered to millions of patients world-wide to treat erectile dysfunction, benign lower urinary tract symptoms and pulmonary arterial hypertension 21, 47 . High dose PDE5i show safety and efficacy for treating heart failure with reduced ejection fraction 48 .…”
Section: Discussionmentioning
confidence: 99%